Estrategias de intervención para el desarrollo turístico sostenible del humedal “La Segua” - Vidal Loor, José Daniel (2019)
The purpose of this research was to design the most optimal intervention strategies for a suitable tourism development without the degradation of the Segua's natural environment. The type of research adopted was mixed, with a descriptive approach, in which four phases were proposed for the implementation of the same, starting with the theoretical foundation of the wetland, allowing to know the most appropriate conceptualizations for the development of intervention strategies, then in phase two, it was possible to carry out the tourist diagnosis where the data of the infrastructure, roads and services was obtained, which has this area, and it was found that it is very favorable for an adequate development in the tourist area, in this phase some Surveys to tourists and local comuneros, in order to measure the level of satisfaction of the visitors and the support that is available from the governments of the day. Through phase three it was possible to verify the potential of the La Segua wetland, this was obtained through several instruments (Leopold, direct observation, SWOT, crossed impacts, etc.), and demonstrated the potential of the wetland, and Finally, phase four was carried out, where it was possible to develop the most appropriate strategies in the field of service. Environmental, advertising, human resources and product, each of them focused on tourism development, for this was done a validation of experts to get the views of a group of professionals focused on the environment of the Segua wetland.